EFFECT OF p-AMINOBENZOIC ACID ON THE MICROBIOLOGICAL ASSAY FOR NICOTINIC ACID - Harris Isbell (1942)
In our hands, the treatment of acid hydrolysates of casein with activated charcoal for the removal of traces of nicotinic acid' has always resulted in preparations which do not permit as great acid production by Lactobacillus arabinosus 17-5 as do hydrolysates which are not treated with charcoal.In a typical experiment four aliquots of one lot of an acid hydrolysate of casein containing 100 mg. of dry matter per ml.were treated with 10 mg. per ml. of darco G-60, norit A, nuchar, and carbex E charcoals.The maximum amounts of 0.1 N acid produced in 10 ml. of media based on these charcoal-treated hydrolysates were respectively 3.9, 8.5, 6.9, and 7.8 ml., as compared to 10.5 ml. in a medium based on untreated hydrolysate.Furthermore, the curves of the response of the organism to increasing amounts of nicotinic acid in media prepared with charcoal-treated hydrolysates did not parallel the curves obtained in media based on untreated hydrolysates.If assays were performed on crude extracts of various materials with charcoal-treated caseins used in the assay medium, the results obtained at various levels did not agree, but increased as increasing amounts of the crude extracts were added to the assay tubes.Elution of the charcoal which had been used in treating a casein hydrolysate with hot water at neutral or alkaline pH and addition of the eluate to the charcoal-treated hydrolysate restored the ability of the hydrolysate to support maximum growth.Addition of any one of a number of supposedly pure compounds to a medium based on a hydrolysate which had been treated with 20 mg. per ml. of darco G-60 resulted in as good acid production as was obtained in a medium based on the untreated hydrolysate.The compounds and the minimum amounts of each required to support maximum growth were pimelic acid 50 7, inositol 100 y, choline hydrochloride 50 7,.thymus nucleic acid 10 y, adenosine 50 y, xanthine 50 y, one brand of arginine monohydrochloride 1 mg.(another brand of arginine was without effect), and p-aminobenzoic acid 0.001 y.It will be noted that p-aminobenzoic acid is 10,000 times as active as the next most active compound.This fact suggests that p-aminobenzoic acid is a true growth factor for Lactobacillus arabinosus 17-5.Purification of all the compounds exhibiting activity will be necessary to prove or disprove the specificity of p-aminobenzoic acid.Addition of 1 y of p-aminobenzoic acid to 10 ml. of media based on